Viridans streptococcal infective endocarditis associated with fixed orthodontic appliance managed surgically by mitral valve plasty: A case report. Issue 27 (July 2018) - Birlutiu, Victoria; Birlutiu, Rares Mircea; Costache, Victor Sebastian
Abstract: Rationale: Streptococcus viridans, a heterogeneous group of alpha-hemolytic streptococci, is part of the normal flora of the mouth, usually responsible for dental caries ( Streptococcus mutans, Streptococcus sanguinis ), and pericoronitis, as well as for subacute infective endocarditis. They are responsible for 40-60% of the endocarditis cases occurring on the normal valves, especially in male patients and over 45 years of age. A change in the bacterial flora of the oral cavity is taking part after orthodontic fixed appliances are introduced into the oral cavity, change that is associated with an increased concentration of the acidogenic bacteria. Bacteraemia is the consequence of oral cavity infections, the association of infective endocarditis with fixed orthodontic appliance, as it has been described by us for the first time, caused by Abiotrophia defectiva . Patient concerns: We present the case of a female Caucasian patient, aged 22 years, who developed infective endocarditis with Streptococcus viridans associated with fixed orthodontic appliance, located on the mitral valve, without previous cardiac pathology, and the therapeutic difficulties associated with allergic reactions (to vancomycin, and spironolactone). Diagnoses: Repetitive haemocultures were positive with Streptococcus viridans, while transthoracic echography revealed a severe mitral failure through anteromedial segment of the anterior mitral valve leaf prolapse with eccentric jet to the posterior wall. Interventions: During hospitalization, the decision to undergo surgical intervention was taken after obtaining negative haemocultures. The patient underwent surgically intervention, and a mitral valve plasty with insertion of neochords was performed. Outcomes: Intraoperative and subsequently post-discharge transesophageal echography, highlighted normofunctional mitral plasty with a remaining regurgitation grade I-II of IV, with good openness, minor tricuspid regurgitation, and mild pulmonary hypertension. Lessons: Endocarditis with oral streptococci associated with fixed orthodontic appliance seems to be not so unlikely even in young or without previous cardiac pathology patients, requiring attention in identifying possible pre-existing cardiac conditions like mitral valve prolapse with clinical and echographic monitoring of such cases. Educating and motivating the patient to observe the oral hygiene represent key steps for an optimal oral health during orthodontic treatment. Mechanical tooth cleaning helps maintaining a good oral hygiene during fixed orthodontics and decreasing the oral health risks.